Causes of divorce and its effects on the Omani Family: (Qualitative study) - Al-Alawi, Aisha Rashid; Al-Gharaibeh, Fakir (Al-Adab Journal, 2021)
The current study aimed to identify the causes that lead to divorce and its effects in the Omani families. In order to suggest proposals to reduce divorce in Omani society. The current study is based on the qualitative approach, through analyzing the statistical data of the official statistics of the Omani Ministry of Justice and the statistics of the National Center for Statistics and Information, in addition of interviews with a group of specialists from social researchers and family counseling and guidance specialists in the family development departments in the various governorates of the Sultanate. The results of this study showed that the age groups most exposed to divorce are the young, from 20 to 30 years old and in their first five years of marriage. The factor of poor marital choice, poor marital compatibility, lack of independent housing, and the inability to conceive are considered the most prominent social, economic and health reasons for divorce among spouses in Omani society. The study found that the most dangerous effects resulting from divorce fall on children, then on divorced women, especially mothers. The severity of these effects is evident in the psychological damage that children suffer which in turn affects their educational, behavioral and psychological status and causes them to be emotionally deprived. The study presented some proposals to reduce the phenomenon of divorce in Omani society, including intensifying societal awareness of the importance of marital choice for both the young man and woman. In addition, educating youth before marriage with the skills of managing marital disputes, the appropriate spending policy and how to understand the other partner, in order to achieve the suitable marital compatibility. The mandatory medical examination before marriage for its importance in the stability of the family.